2017
DOI: 10.4274/jtgga.2017.0071
|View full text |Cite
|
Sign up to set email alerts
|

Role of hormones in hypoactive sexual desire disorder and current treatment

Abstract: Over the decades, female sexual dysfunction (FSD) has grown to be an increasingly potential problem that complicates the quality of life among women. In the current review, FSD refers to recurrent and persistent problems with sexual orgasm, desire, or response. One of the most common subtypes of FSD that has evoked increased research interest in the scientific community is hyposexuality. Today, there is a consensus that hyposexuality is a multifactorial condition that manifests with reduced sexual desire resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 85 publications
(103 reference statements)
1
15
0
Order By: Relevance
“…A loss of sexual interest may be caused by a dramatic decrease in oestrogen levels due to curative cancer treatment [ 31 ], which has been shown to be associated with the occurrence of vaginal dryness and dyspareunia. These symptoms reduced the patients’ desire for sexual activities and decreased the frequency of sexual activity with their partners [ 32 ], as reported by some participants of our study. Furthermore, the patients in our study reported a poorer body image, consistent with the findings of a previous study [ 13 ], and a sense of being an imperfect woman.…”
Section: Discussionsupporting
confidence: 78%
“…A loss of sexual interest may be caused by a dramatic decrease in oestrogen levels due to curative cancer treatment [ 31 ], which has been shown to be associated with the occurrence of vaginal dryness and dyspareunia. These symptoms reduced the patients’ desire for sexual activities and decreased the frequency of sexual activity with their partners [ 32 ], as reported by some participants of our study. Furthermore, the patients in our study reported a poorer body image, consistent with the findings of a previous study [ 13 ], and a sense of being an imperfect woman.…”
Section: Discussionsupporting
confidence: 78%
“…Technically, the young uniform services personnel posted for peacekeeping are young, energetic trained risk-taking o cers within their early 20s and 30s, the most vulnerable group to HIV infection. Also, biologically younger o cers in their early 20s and 30s experienced high secretion of sex hormones (testosterone and progesterone), making them sensitive to sexual desire (Agaba et al, 2016;AlAwlaqi, Amor, & Hammadeh, 2017). Coincidently, this same age group posted outside their homes and immediate families for a very long period represents the most vulnerable age affected by HIV/AIDS (CDC, 2018a;CDC, 2018b;UNAIDS, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A portion of patients think that their condition is a part of their normal lives, and discharge is physiologic, because discharge is not always vexing. Sometimes discharge is seen only in small amounts that only smudges on the vaginal walls and labia, it can be in excessive amounts that will lead the patient to make a visit for examination and to accumulate in the posterior fornix [3].…”
Section: Discussionmentioning
confidence: 99%
“…While the most frequent complaints at presentation are vaginal discharge and bad odor that irritate the couple during sexual intercourse, complaints about the sense of disgust and lack of pleasure from the intercourse are mentioned more when the anamnesis is deepened somehow. This in turn affects the sexual lives of patients and can result in sexual dysfunction in patients [3].…”
Section: Introductionmentioning
confidence: 99%